Training Of Learning Strategies in Writing Essay - Winarto, Agus Edi (JEELS (Journal of English Education and Linguistics Studies), 2015)
Writing essay is still considered difficult for English students to master. The students are expected to be able to express their ideas correctly without making any chance of messages to be misinterpreted by the readers; therefore, they have to know and use the best or the most appropriate ways to write. The purpose of writing this article is to introduce learning strategies and the possibility of training of learning strategies in writing essay to English students. The first strategy is integration of strategy with the process of writing essay: pre-writing, writing draft, and post-writing activities. The second is training learning strategies, such as memory, cognitive, compensation, metacognitive, affective, and social strategies to students to make writing essay easier, faster, more enjoyable, more effective, and more self-directed to achieve the desired result in their writing. To get better result of improvement, the model of training of learning strategies in writing essay should be applied and developed based on the appropriateness of teachers, learners, subjects, and situations.